Gut dysbiosis in patients with chronic pain: a systematic review and meta-analysis - Goudman, Lisa; Demuyser, Thomas; Pilitsis, Julie G.; Billot, Maxime; Roulaud, Manuel; Rigoard, Philippe; Moens, Maarten (Frontiers in Immunology, 2024)
Recent evidence supports the contribution of gut microbiota dysbiosis to the pathophysiology of rheumatic diseases, neuropathic pain and neurodegenerative disorders. The bidirectional gut-brain communication network and the occurrence of chronic pain both involve contributions of the autonomic nervous system and the hypothalamic pituitary adrenal axis. Nevertheless, the current understanding on the association between gut microbiota and chronic pain is still not clear. Therefore, the aim of this study is to systematically evaluate the existing knowledge about gut microbiota alterations in chronic pain conditions.Methods. Four databases were consulted for this systematic literature review: PubMed, Web of Science, Scopus, and Embase. The Newcastle-Ottawa Scale was used to assess the risk of bias. The study protocol was prospectively registered at the International prospective register of systematic reviews (PROSPERO, CRD42023430115). Alpha-diversity, β-diversity and relative abundance at different taxonomic levels were summarized qualitatively, and quantitatively if possible.Results. The initial database search identified a total of 3544 unique studies, of which 21 studies were eventually included in the systematic review and 11 in the meta-analysis. Decreases in alpha-diversity were revealed in chronic pain patients compared to controls for several metrics: observed species (SMD= -0.201, 95% CI from -0.04 to -0.36, p=0.01), Shannon index (SMD= -0.27, 95% CI from -0.11 to -0.43, p<0.001), and faith phylogenetic diversity (SMD -0.35, 95% CI from -0.08 to -0.61, p=0.01). Inconsistent results were revealed for beta-diversity. A decrease in relative abundance of Lachnospiraceae family, genus Faecalibacterium and Roseburia, and species of Faecalibacterium prausnitzii and Odoribacter splanchnicus as well as an increase in Eggerthella spp. was revealed in chronic pain patients compared to controls.Discussion. Indications for gut microbiota dysbiosis were revealed in chronic pain patients, with non-specific disease alterations of microbes.